The Efficacy of Using Quizzing Collaborative Learning Strategy in Teaching Grammar to Senior High School Students - Soleman Dapa Taka (Institut Agama Islam Negeri Palopo, 2022)
This research aims at finding out the efficacy of using Quizzing Collaborative Learning Strategy in teaching grammar especially conditional sentences to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of Quizzing Collaborative Learning Strategy effective in teaching grammar to Indonesian EFL students?. The research can be an addition to the persisting teaching grammar of English particularly the use of Quizzing Collaborative Learning Strategy. This research was conducted at the tenth-grade students at SMA Kristen Mercusuar, Kupang, an Indonesian High School. The total number of samples was 25 students. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in reading and the post-test given to find out the students’ improvement in grammar especially passive voice after giving the treatment by using Quizzing Collaborative Learning Strategy. The findings show that using the Quizzing Collaborative Learning Strategy is effective in teaching grammar to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use the Quizzing Collaborative Learning Strategy in developing students’ competence in grammar class of Indonesian EFL students.